PENGARUH GAYA KEPEMIMPINAN DAN PROMOSI JABATAN TERHADAP MOTIVASI KERJA KARYAWAN PT. NAGA HARI UTAMA MEDAN - Imelda Imelda; Imanuel Tarigan; Syawaluddin Syawaluddin (JURNAL BISNIS KOLEGA, 2021)
Leadership style is : a pattern of behavior of a leader in influencing employees to work in accordance with the directions given. Job Promotion is: an increase in a position to a higher position followed by greater duties and responsibilities, higher authority and higher salary than the previous position. Work motivation is : an encouragement in a person to do a job better.The research method used is quantitative data analysis method. The data used are primary and secondary data. The research population was 39 people using a saturated sampling technique where all members of the population were sampled. Variables were measured using a Likert scale. The data analysis technique used is multiple linear regression. Based on the simultaneous analysis of Leadership Style and Job PromotionÂ  effect the Work Motivation of Employees of PT. Naga Hari Utama Medan. Partially, there is no influence of the leadership style variable on the work motivation of employees of PT. Medan Main Day Dragon. Partially, there is no effect of Job Promotion variable on Employee Work Motivation of PT. Naga Hari Utama MedanÂ Keywords : Leadership Style, Job Promotion and Work Motivation